Cognitive enrichment improves spatial memory and alters hippocampal synaptic connectivity in a mouse model for early-life stress - Shobe, Justin L.; Ghanbarian, Elham; Bain, Robert; Saxena, Rajat; Chandrasekaran, Meenakshi; McNaughton, Bruce L. (Frontiers in Cellular Neuroscience, 2025)
Early-life stress (ELS) and enrichment often have opposing effects on long-term cognitive abilities. Deprivation, such as institutionalized care during early childhood neurodevelopmental periods, results in lifelong working memory and recall deficits. In contrast, enrichment facilitates new learning and slows cognitive decline due to aging and neurodegenerative diseases. Similarly, in rodent models, enrichment facilitates learning whereas ELS induces prominent spatial memory deficits. Environmental enrichment (EE) and ELS can cause opposing changes in hippocampal structure (e.g., shifts in synaptic density) that largely depend on experimental conditions. However, it remains untested whether EE can rescue the behavioral disruptions caused by ELS and how this would impact the hippocampus at advanced ages. To address this, we conducted a longitudinal study on ELS mice, extensively training them on a cognitive enrichment track (ET) or an exercise alone control track (CT). After this, the mice underwent repeated memory testing followed by brain extraction for anatomical analysis of their hippocampus. We found that ET reversed spatial memory deficits at 6, 13, and 20 months and reduced the number of dentate gyrus (DG) to CA3 synapses. Surprisingly, this reduction occurred at excitatory MF synapses surrounding CA3 somas in the stratum pyramidale—a layer not typically associated with MF terminals. Collectively, these findings suggest that cognitive enrichment during early adulthood may reverse ELS-induced spatial memory deficits by adjusting synaptic connectivity between the DG and CA3.